Peningkatan Keaktifan Belajar dan Kemandirian Belajar IPS melalui Media Pembelajaran Liveworksheet pada Peserta Didik Kelas VIIA di SMP - Sinta Fepiana; Salamah Salamah (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to increase learning activity and independence in social studies learning through live worksheet learning media for class VII A students in junior high school. This research is a classroom action research with the research subjects are students of class VII A in junior high school. This research will be carried out in two cycles, the first cycle consists of two meetings and the second cycle consists of two meetings. At the end of each cycle an evaluation is carried out. Data collection in this action research is done by observation, documentation and learning outcomes tests. True learning throughout the life of students, one of which is indicated by an attitude of activeness, independence in learning and an increase in learning outcomes. The activeness of students when learning is all learning activities that involve students, both physical and non-physical in the learning process that can encourage students to be more critical, express opinions in discussions, ask questions, and be able to solve a given problem. Independence is an attempt to break away from parents with the intention of finding oneself through the process of seeking ego identity, which is a development towards a stable and independent individuality. Based on the conclusion, there is an increase in learning activity and independence in social studies learning through live worksheet learning media for class VII A students in junior high school.